Leaping lizards - Murphy, Stuart J., 1942-; Adinolfi, JoAnn (New York : HarperCollins, 2005)
A group of lizards are late for their big performance, until then start arriving in groups of five. Presented in simple rhyming text and illustrations and introduces the basic math concept of counting by five.
"Counting by 5s and 10s, Level 1.".
Booklist.
Horn Book.
Wilson's Children.
1.4
K-3
Keywords: Addition -- Juvenile literature; Counting -- Juvenile literature; Addition; Counting; Addition; Counting; Stories in rhyme